Awareness and Constraints Regarding Water Conservation Practices in Haryana (India) - Kumar, Pawan; Mukteshawar, Rati; Rani, Sonia; Malik, J S; Kumar, Narender (Indian Journal of Extension Education, 2025)
Water and soil are the most important inputs essential for crops. Both shortage and excess of water affects the growth and development of the plants, yields and quality of produce.Â There are numerous methods to reduce such losses and to improve soil moisture like mulching, cropping pattern, planting of trees and water harvesting etc. The study was carried out in two agro-climatic zone i.e. north-eastern zone and south-western zone ofÂ Haryana state. A total 240 farmers were interviewed with well-structured interview scheduleÂ for awareness and constraints regarding water conservation practices. The findings revealed that farmersâ€™ had high awareness about â€˜canal water is best for cropsâ€™, â€˜nearness of soilÂ and water testing laboratoryâ€™ and â€˜water harvesting reduce soil erosionâ€™. The majorÂ constraints reported by farmers were â€˜Lack of soil and water testing facilities and delay inÂ reportsâ€™ and â€˜Deterioration of water quality in indigenous water harvesting structureâ€™.